2004
DOI: 10.4064/sm162-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Boundedness properties of fractional integral operators associated to non-doubling measures

Abstract: Abstract. The main purpose of this paper is to investigate the behavior of fractional integral operators associated to a measure on a metric space satisfying just a mild growth condition, namely that the measure of each ball is controlled by a fixed power of its radius. This allows, in particular, non-doubling measures. It turns out that this condition is enough to build up a theory that contains the classical results based upon the Lebesgue measure on Euclidean space and their known extensions for doubling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 21 publications
1
101
0
3
Order By: Relevance
“…[d(x,y)] n−β(x) of a constant is a bounded function, which is known, see for instance [15], Lemma 2.1, and is easily verified via the standard decomposition…”
Section: Dµ(y)mentioning
confidence: 94%
See 3 more Smart Citations
“…[d(x,y)] n−β(x) of a constant is a bounded function, which is known, see for instance [15], Lemma 2.1, and is easily verified via the standard decomposition…”
Section: Dµ(y)mentioning
confidence: 94%
“…We prove two versions of Sobolev-type theorems with variable exponents. Various versions of such theorems for constant p were proved in [18], [15], [16], [17], [30], [31]. We also give boundedness statements for corresponding fractional maximal operators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently more attention has been paid to non-doubling measures. It has been shown that many results of this theory still hold without assuming the doubling property; see [16,17,18,19,23,24,25,29,5,6] for some results on Calderón-Zygmund operators, [15,26,27,28] for some other results related to the spaces BM O(µ) and H 1 (µ), and [7,8,20] for the vector-valued inequalities on the Calderón-Zygmund operators and weights. …”
Section: Introductionmentioning
confidence: 99%